Assessing Genetic Diversity Cocoa (Theobroma cacaoL.) Collection Resistant to Cocoa Pod Borer Using Simple Sequence Repeat Markers - Agung Wahyu Susilo; Dapeng Zhang; Lambert Motilal (Indonesian Coffee and Cocoa Research Institute, 2013)
Breeding for cocoa pod borer (CPB) resistance on cocoa was initiated by selecting the resistant genotypes through cocoa farm in the endemic area. For breeding purpose the collected genotypes should be assessed for their diversity in constructing appropriate mating design. This research has objective to assess genetic diversity of the exploratory collection using DNA fingerprinting. The tested clones were 25 exploratory collections compared to the references of seven international clones from International Cocoa Genebanks, Trinidad and12 national clones. DNA of the tested clones was sequenced using 15 SSR markers at Sustainable Perennial Crop Laboratory of Beltsville Agriculture Research Center.Data of fingerprinting were analyzed using GenAlEx program to perform number of alleles, observed heterozygosity (Ho), expected heterozygosity (He) and genetic distance. The tested clones performed high genetic diversity with the number of alleles was 98 (6.53 per locus) compared to the national clones andinternational clones were 95 (6.33 per locus) and 86 (5.73 per locus), respectively. The observed heterozygosity of the tested clones (Ho = 0.63) was higher thannational clones (Ho = 0.60) and international clones (Ho = 0.49) then supported by the expected heterozygosity (He) of the tested clones (He = 0.71) also highin equal value with international clones (He = 0.74). Cluster analysis grouped the tested clones to three main genetic groups, namely Trinitario, Forastero and unidentified group. The CPB-resistant clones of ARDACIAR 10 and KW 397 were clustered in different group that indicate a far distance of their genetic background.Key words:Genetic diversity, cocoa, CPB resistance, simple sequence repeat marker.